Generation of periventricular reactive astrocytes overexpressing aquaporin 4 Is stimulated by mesenchymal stem cell therapy - García-Bonilla, María; Ojeda-Pérez, Betsaida; Shumilov, Kirill; Rodríguez-Pérez, Luis Manuel; Domínguez-Pinos, Dolores; Vitorica Ferrández, Javier; Jiménez, Sebastián; Ramírez-Lorca, Reposo; Echevarría, Miriam; Cárdenas García, Casimiro; Iglesias, Teresa; Gutiérrez-Pérez, Antonia; et al. (MDPI, 2023)
Aquaporin-4 (AQP4) plays a crucial role in brain water circulation and is considered a therapeutic target in hydrocephalus. Congenital hydrocephalus is associated with a reaction of astrocytes in the periventricular white matter both in experimental models and human cases. A previous report showed that bone marrow-derived mesenchymal stem cells (BM-MSCs) transplanted into the lateral ventricles of hyh mice exhibiting severe congenital hydrocephalus are attracted by the periventricular astrocyte reaction, and the cerebral tissue displays recovery. The present investigation aimed to test the effect of BM-MSC treatment on astrocyte reaction formation. BM-MSCs were injected into the lateral ventricles of four-day-old hyh mice, and the periventricular reaction was detected two weeks later. A protein expression analysis of the cerebral tissue differentiated the BM-MSC-treated mice from the controls and revealed effects on neural development. In in vivo and in vitro experiments, BM-MSCs stimulated the generation of periventricular reactive astrocytes overexpressing AQP4 and its regulatory protein kinase D-interacting substrate of 220 kDa (Kidins220). In the cerebral tissue, mRNA overexpression of nerve growth factor (NGF), vascular endothelial growth factor (VEGF), hypoxia-inducible factor-1 (HIF1α), and transforming growth factor beta 1 (TGFβ1) could be related to the regulation of the astrocyte reaction and AQP4 expression. In conclusion, BM-MSC treatment in hydrocephalus can stimulate a key developmental process such as the periventricular astrocyte reaction, where AQP4 overexpression could be implicated in tissue recovery.
Keywords: Hidrocefalia - Tratamiento; Células madre - Uso terapéutico; Terapia celular; Medicina regenerativa; Experimentación animal; Hydrocephalus; Aquaporin 4; Astrocyte reaction; Mesenchymal stem cell; Stem cell therapy; Proteomic